A daily representation of Great Britain’s energy vectors: natural gas, electricity and transport fuels - I. A. Grant Wilson; Anthony J. R. Rennie; Peter J. Hall; Nicolas J. Kelly (ACI Avances en Ciencias e Ingenierías, 2014)
In much of Europe there is a strong push to decarbonize energy demands, including the largest single end-use demand, which is heat. Moving heat demands over to the electrical network poses significant challenges and the use of hybrid energy vector and storage systems (heat and electrical storage) will be a critical component in managing this transition. As an example of the challenges facing many developed countries, the scale of recently available daily energy flows through the UK’s electrical, gas and transport systems are presented. When this data is expressed graphically it illustrates important differences in the demand characteristics of these different vectors; these include the quantity of energy delivered through the networks on a daily basis, and the scale of variability in the gas demand over multiple timescales (seasonal, weekly and daily). As the UK proceeds to migrate heating demands to the electrical network in its drive to cut carbon emissions, electrical demand will significantly increase. Additionally, the greater variability and uncertainty shown in the gas demand will also migrate to the electrical demand, posing significant difficulties for the maintenance of a secure and reliable electrical system in the coming decades. This paper concludes with an analysis of the different means of accommodating increasingly volatile electricity demands in future energy networks.